The Economic Functions of Government Expounded in Al-’Iqtiṣādu l-’Islāmī of At-Turkī: A Lesson for Policy-Makers in Nigeria - Yahya, Shaykh Ahmad (IAIN Parepare, 2024)
Al-Iqtiṣādu’l-’Islāmī:’Ususun wamabādi’u wa ’ahdāf is one of the classical works written to unveil the Islamic mechanism to regulate fiscal relations on the basis of the Qur’ān and Sunnah. This paper, therefore, aims at studying one of the chapters of the work that focuses on the economic functions of Islamic government with a view to unfold the tools needed to turn around the economy of Nigeria and accentuate the necessity of formulating robust economic policies that are friendly to the down trodden masses as emphasised in the work. At-Turki, in this work, strived to proffer solution to the economic problems of the world including Nigeria by highlighting the roles anticipated from the progressive government aspiring to attain stable prices, full employment and economic growth. Through phenomenological method, the work observed that the Nigerian government aligned with some Islamic economic policies despite the fact that it is a multi-religious nation but the bane experienced in the economy is not unconnected to its failure to key into the functions totally. The work recommends utilisation of the propositions of At-Turki since they are divinely guided and submitted that legalisation of the commodities that are diametrically opposed to the divine Book recede economic growth.